2020
DOI: 10.5194/gmd-13-3769-2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CH4MOD<sub>wetland</sub> and Terrestrial Ecosystem Model (TEM) used to estimate global CH<sub>4</sub> emissions from natural wetlands

Abstract: Abstract. Wetlands are the largest and most uncertain natural sources of atmospheric methane (CH4). Several process-based models have been developed to quantify the magnitude and estimate spatial and temporal variations in CH4 emissions from global wetlands. Reliable models are required to estimate global wetland CH4 emissions. This study aimed to test two process-based models, CH4MODwetland and Terrestrial Ecosystem Model (TEM), against the CH4 flux measurements of marsh, swamp, peatland and coastal wetland s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…As the model combination was fully parametrized and validated at multiple inland and coastal wetland sites across China and around the world, we followed the parametrization in previous studies. , The calibrated parameters are mainly related to the different capabilities of CH 4 production, oxidation, and transportation between herbaceous and woody plants, as well as the influence of salinity in coastal wetlands. The DISCover database was used to assign the woody or herbaceous plants.…”
Section: Methodsmentioning
confidence: 99%
“…As the model combination was fully parametrized and validated at multiple inland and coastal wetland sites across China and around the world, we followed the parametrization in previous studies. , The calibrated parameters are mainly related to the different capabilities of CH 4 production, oxidation, and transportation between herbaceous and woody plants, as well as the influence of salinity in coastal wetlands. The DISCover database was used to assign the woody or herbaceous plants.…”
Section: Methodsmentioning
confidence: 99%
“…Although the total surface area of natural wetlands is only a small part of the land area, they are the largest source of global CH 4 emissions. Global wetland CH 4 emissions are approximately 116.99-124.74 Tg•yr −1 , which has a huge impact on global climate change according to the latest estimation models [7]. CH 4 produced in nature will reduce its emissions due to the oxidation-reduction reaction between microorganisms and various electron receptors under aerobic or anaerobic conditions before being discharged into the atmosphere [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the AOM process involves several different electron acceptors, including sulfate (SO 4 2− ), nitrate/nitrite (NO 3 − /NO 2 − ), and metal ions (Mn 4+ , Fe 3+ ), called sulfate-based methane anaerobic oxidation (SAMO), nitrate-based methane anaerobic oxidation (n-DAMO), metal-ionic methane anaerobic oxidation (Metal-AOM), and direct interspecies electron transfer (DIET), respectively. Current domestic and international studies on AOM processes in natural wetlands have mostly focused on peatlands [18][19][20], mangrove wetlands [21], rice fields [7,[22][23][24], Yangtze River crossing wetlands [25,26], and the Minjiang River estuary wetlands [27,28]. In contrast, the Yellow River Delta is the youngest and most complex coastal wetland in the warm temperate zone of China.…”
Section: Introductionmentioning
confidence: 99%